2018
DOI: 10.1111/ivb.12212
|View full text |Cite
|
Sign up to set email alerts
|

Benthic ctenophores (Platyctenida: Coeloplanidae) in South Florida: predator–prey interactions

Abstract: The primary goal of this study was to demonstrate, from field observations and laboratory experiments, some key trophic roles of benthic ctenophores as predators and prey in subtropical communities. We examined individuals of two benthic platyctenid species: Coeloplana waltoni, a minute epibiont on octocorals in exposed, open‐water settings; and Vallicula multiformis, an associate of calm‐water biofouling communities and floating Sargassum spp. Laboratory observations of individuals of both ctenophore species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Bavestrello et al (1996) observed caprellids seizing previously captured nauplii from hydroid polyps; a nudibranch grazing preferentially on hydroid polyps that previously ingested zooplankton, an example of the consumption of a prey item plus its ingested prey, was termed kleptopredation by Willis et al (2017). The symbiotic status of the benthic ctenophore and its octocoral host is not clear since we have observed the ctenophore purloining food (unidenti ed organic detritus) captured by its host's polyps, and octocoral polyps have been observed removing captured sh eggs from the tentacles of ctenophore epizoites (Glynn et al 2018a). Further study is necessary to determine the signi cance of these trophic resources, the relative amounts garnered by the symbiotic partners, and how eld conditions affect these interactions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Bavestrello et al (1996) observed caprellids seizing previously captured nauplii from hydroid polyps; a nudibranch grazing preferentially on hydroid polyps that previously ingested zooplankton, an example of the consumption of a prey item plus its ingested prey, was termed kleptopredation by Willis et al (2017). The symbiotic status of the benthic ctenophore and its octocoral host is not clear since we have observed the ctenophore purloining food (unidenti ed organic detritus) captured by its host's polyps, and octocoral polyps have been observed removing captured sh eggs from the tentacles of ctenophore epizoites (Glynn et al 2018a). Further study is necessary to determine the signi cance of these trophic resources, the relative amounts garnered by the symbiotic partners, and how eld conditions affect these interactions.…”
Section: Discussionmentioning
confidence: 87%
“…Since octocorals engage heavily in suspension feeding, capturing particulate organic matter (Lasker, 1981) and microzooplankton (Glynn et al 2018a), the interference of polyp expansion by individuals of O. mirabilis was suggested to be a potentially signi cant threat against satisfying the trophic requirements of octocoral hosts (Araújo et al 2018;Ferry et al 2020), although a recent study suggests this may not be consequential (Glynn et al, 2021). From the current study --which has demonstrated an inverse relationship in the abundance of ophiuroids and ctenophores in eld collections, and decreasing ctenophore abundance in the presence of ophiuroids in a laboratory experiment --it appears that the major effect of the exotic ophiuroid is on the displacement, by interference competition, of the cohabiting benthic ctenophore.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is in need of further investigation. Sporadic declines of V. multiformis are possibly related to predation (Glynn et al, ) or low organic production and a scarcity of trophic (zooplankton) resources. Alamaru et al () reported maximum abundances of V. multiformis in the Gulf of Aqaba (Red Sea) in the winter season during water column mixing and massive algal blooms.…”
Section: Discussionmentioning
confidence: 99%
“…When fishing, the tentacles can extend to at least 5-10 times the body length, capturing mesozooplankton, both holoplankton and meroplankton. These planktonic components often include fish eggs and larvae (Glynn et al 2018), both of which play a crucial role in population counts of many species. Studies have generally focused on the predatory behavior of benthic ctenophores with the functional role of tentacles involved in the capture of zooplankton (Rankin 1956, Emson and Whitfield 1991, Eeckhaut et al 1997.…”
mentioning
confidence: 99%
“…Agitation or predator simulation was effected by pricking ctenophores, dislodging them from a resting position by forceful water jets, and probing with a cheliped of a known crab predator [Portunus sayi (Gibbes 1850)]. Additionally, naturally occurring live predators of V. multiformis, the sea anemone Exaiptasia pallida (Agassiz in Verrill, 1864), and of C. waltoni, the gastropod mollusk Cyphoma gibbosum Linnaeus 1758 and the pygmy angelfish Centropyge argi Woods & Kanazawa 1951, were offered ctenophore prey (see Glynn et al 2018 Individuals of V. multiformis remained motionless under low light and low flow to still water conditions. In feeding trials, tentacle extension occurred in a matter of minutes in flowing water with zooplankton.…”
mentioning
confidence: 99%